Exploring the role of low level visual processing in letter-speech sound integration: a visual MMN study - Froyen, Dries; Van Atteveldt, Nienke; Blomert, Leo (Frontiers in Integrative Neuroscience, 2010)
In contrast with for example audiovisual speech, the relation between visual and auditory properties of letters and speech sounds is artificial and learned only by explicit instruction. The arbitrariness of the audiovisual link together with the widespread usage of letter–speech sound pairs in alphabetic languages makes those audiovisual objects a unique subject for crossmodal research. Brain imaging evidence has indicated that heteromodal areas in superior temporal, as well as modality-specific auditory cortex are involved in letter–speech sound processing. The role of low level visual areas, however, remains unclear. In this study the visual counterpart of the auditory mismatch negativity (MMN) is used to investigate the influences of speech sounds on letter processing. Letter and non-letter deviants were infrequently presented in a train of standard letters, either in isolation or simultaneously with speech sounds. Although previous findings showed that letters systematically modulate speech sound processing (reflected by auditory MMN amplitude modulation), the reverse does not seem to hold: our results did not show evidence for an automatic influence of speech sounds on letter processing (no visual MMN amplitude modulation). This apparent asymmetric recruitment of low level sensory cortices during letter–speech sound processing, contrasts with the symmetric involvement of these cortices in audiovisual speech processing, and is possibly due to the arbitrary nature of the link between letters and speech sounds.